The Role of Sirt1 in Ischemic Stroke: Pathogenesis and Therapeutic Strategies - Zhang, Jun-Fang; Zhang, Yu-Lei; Wu, Yun-Cheng (Frontiers in Neuroscience, 2018)
Silent mating-type information regulation 2 homolog 1 (Sirt1)，a nicotine adenine dinucleotide (NAD+)-dependent enzymes，is well known in playing a part in longevity. Ischemic stroke is a major neurological disorder and a leading cause of death and disability worldwide. Recently, many studies have been focused on the role of Sirt1 in ischemic stroke. A plenty of studies consider Sirt1 as a protective factor and investigate the signaling pathways involved in the process under ischemic stress. However, whether upregulation of Sirt1 improves stroke outcome is still controversy. In this review, we will discuss the role and mechanisms of Sirt1 in the setting of ischemic stroke.